Pendekatan Dalam Penguatan Pendidikan Karakter (PPK) di SD Muhammadiyah 8 KH. Mas Mansyur Kota Malang - Widodo, Rohmad; Mansur, M (Universitas Nusantara PGRI Kediri, 2022)
This study aims to describe the basic concepts of strengthening character education in SD Muhammadiyah 8 KH. Mas Mansyur Malang City. This research uses a descriptive approach. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used the Miles and Huberman technique which consisted of data collection, data reduction, data analysis and conclusions. While the validity of the data used is triangulation test. The results showed that: improving character education through cultural development in schools was done by developing a culture of salim before entering class, developing a 3-S culture (greetings, greetings and smiles), washing hands and praying before and before eating, having a healthy breakfast together, loving the environment. and literacy movement. Strengthening character education through self-development activities in the form of Scouts, Pencak Silat, the art of reading the Qur'an, Iqra', Adhan, Speech and the art of calligraphy. Strengthening integrated character education through learning, where each teacher provides character strengthening through the subjects taught.